2019
DOI: 10.1186/s13287-019-1462-z
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-2 stimulates proliferation of human adipose-derived stem cells via Src activation

Abstract: BackgroundHuman adipose-derived stem cells (hASCs) are a subset of mesenchymal stem cells (MSCs); it has been regarded as one of the most promising stem cells. We previously found that fibroblast growth factor-2 (FGF-2) enhanced the proliferation and differentiation of hASC. However, the mechanisms involved in the growth of hASCs by FGF-2 have not been investigated.MethodsHuman adipose-derived stem cells (hASCs) were cultured with FGF-2, and cell growth was assessed. Effects of FGF Receptor (FGFR) inhibitor (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…bFGF participates in proliferation and self‐renewal of stem cells 38,39 . Previous study demonstrated that 5 ng/mL bFGF effectively enhanced the proliferation of bone marrow mesenchymal stem cells 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bFGF participates in proliferation and self‐renewal of stem cells 38,39 . Previous study demonstrated that 5 ng/mL bFGF effectively enhanced the proliferation of bone marrow mesenchymal stem cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…bFGF participates in proliferation and self-renewal of stem cells. 38,39 Previous study demonstrated that 5 ng/mL bFGF effectively enhanced the proliferation of bone marrow mesenchymal stem cells. 31 And we discovered that 20 ng/mL bFGF significantly boosted up the viability of post-thawed DPSCs, and this advantageous effect emerged at day 5 ( Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FGFR is a family of tyrosine kinases that can activate signaling cascades, such as RAS-MAPK, PI3K-AKT, phospholipase C γ and STAT (48). Among the downstream mediators of FGF2 signaling pathways, the MAPK pathway has been demonstrated to play a pivotal role in the function of stem cells, including mesenchymal stem cells (49)(50)(51). Thus, the present study focused on the MAPK pathway and found that FGF2 induced the phosphorylation of p38 MAPK, ERK1/2 and JNK in SDP11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated and downregulated mRNAs were enriched to GO terms and KEGG pathways. Among all the related pathways, the MAPK signaling pathway, which is also an important pathway regulating ADSC proliferation [ 38 ], differentiation [ 39 ], and migration [ 40 ], had the highest gene ratio in the upregulated mRNA enriched pathways. To screen the three terms related to MAPK signaling pathway, all the BP terms enriched by differential expressed mRNAs were calculated ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%